Knowledge sharing in Islam: implications for practice in organisations - Abdul Hamid, Zabeda (IIUM Press, 2011)
Organisations are currently utilising all their capacity in the turbulent economy to try to maintain competitive advantage. One of the best capitals for an organisation is the knowledge of the employees. However, employees who are experts in their field but do not share their skills or knowledge with other members of the organisation are not going to benefit the company and this situation needs to be rectified. Furthermore, it is an amanah (responsibility) as Muslims to do the best we can in our work and also to share knowledge with others so that we may learn from each other. This chapter will discuss some Islamic perspectives that can affect the knowledge sharing behaviour among employees within organisations. Despite some barriers to sharing knowledge, there are methods that can be implemented to enhance the knowledge sharing process within organisations which is discussed in this chapter. At the same time, some motivational tools will also be presented so that organisations may implement them as a way to enhance the knowledge process within their respective companies.